Ultrasound Elastography Applications in Pediatrics - Thumar, Vishal; Squires, Judy H; Spicer, Paul J; Robinson, Amie L; Chan, Sherwin S (Ultrasound quarterly, 2018)
Ultrasound is one of the most important imaging modalities in pediatric imaging because of its accessibility, portability, lack of ionizing radiation, and ability to generally perform examinations without need for sedation. Ultrasound elastography can measure the stiffness of various tissues. This review article aims to discuss how ultrasound elastography has performed in evaluating multiple pathologies in the pediatric population. The best studied pediatric applications are in liver diseases such as fibrosis, biliary atresia, and hepatic vascular congestion. Measuring muscle stiffness in cerebral palsy is the most promising pediatric musculoskeletal application, but many other applications are in the early stages of research. Other applications in pediatric small organ imaging have been explored and still need more study before gaining clinical relevance.